Pengaruh Dukungan Keluarga dan Keterikatan Karyawan Terhadap Prestasi Kerja Dimediasi oleh Kepuasan Kerja - Ely Kulsum; Jul Aidil Fadli (Economic Reviews Journal, 2025)
Employee performance is an important element in supporting operational effectiveness, especially in the port sector. This study aims to analyze the direct and indirect effects of family support and employee commitment on job performance, with job satisfaction as the mediating variable. The research was conducted on employees of PT. X at Tanjung Priok Port using a quantitative approach and purposive sampling technique, with a sample size of 100 respondents. Data analysis utilized the Structural Equation Modeling method based on Partial Least Squares (PLS-SEM). The results indicated that family support and employee commitment significantly influence job satisfaction. However, neither directly influences job performance significantly. On the other hand, job satisfaction positively and significantly influences job performance and mediates the relationship between independent variables and job performance. Although significant, the strength of the mediating effect is relatively low. These findings indicate that job satisfaction plays a crucial role as a link between psychosocial factors and employee performance. Therefore, organizations should focus on enhancing job satisfaction through supportive policies and work environments to optimize employee performance.